2003
DOI: 10.1161/01.cir.0000057981.70380.45
|View full text |Cite
|
Sign up to set email alerts
|

Atrial High Rate Episodes Detected by Pacemaker Diagnostics Predict Death and Stroke

Abstract: Background-Some current pacing systems can automatically detect and record atrial tachyarrhythmias that may be asymptomatic. We prospectively studied a 312-patient (pt) subgroup of MOST (MOde Selection Trial), a 2010-patient, 6-year randomized trial of DDDR versus VVIR pacing in sinus node dysfunction (SND). The purpose of the study was to correlate atrial high rate events (AHREs) detected by pacemaker diagnostics with clinical outcomes. Methods and Results-Pacemakers were programmed to log an AHRE when the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
262
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 681 publications
(281 citation statements)
references
References 32 publications
5
262
1
13
Order By: Relevance
“…Atrial high-rate episodes are the most common arrhythmia recorded by wireless devices [8,9]. It has previously been shown that atrial high-rate episodes lasting ≥5 min double the risk of stroke or death in patients with sinus node dysfunction who undergo dual-chamber pacemaker implantation [10]. However, there are certain undetermined considerations.…”
mentioning
confidence: 99%
“…Atrial high-rate episodes are the most common arrhythmia recorded by wireless devices [8,9]. It has previously been shown that atrial high-rate episodes lasting ≥5 min double the risk of stroke or death in patients with sinus node dysfunction who undergo dual-chamber pacemaker implantation [10]. However, there are certain undetermined considerations.…”
mentioning
confidence: 99%
“…23 In contrast, another study looking at the duration of atrial high rate events, found that only episodes lasting longer than one day increased risk. 27 The investigators also noted that 12% of the cohort received an ICD shock during the first 3 months after implantation.…”
Section: As Submitted Tomentioning
confidence: 96%
“…22 Furthermore, detection of atrial high-rate events in devices is a predictor of poor outcome. 23 Based on these observations, it is likely that the current estimates of AF prevalence in the general population may eventually be revised upward. Rhythm Classification algorithm) in patients with and without a history of AF.…”
Section: As Submitted Tomentioning
confidence: 99%
“…The threshold for a significant increase of TE risk varied from 5 minutes to 24 hours. [17][18][19][44][45][46][47] It seems reasonable to speculate that the implications of AF burden may be different in patients with different baseline risks, in particular in patients with or without prior stroke. An interesting observation supporting the hypothesis of a multivariable model and the absence of a fixed threshold predictive of increased risk is suggested from a proof-of-concept study in which the risk of stroke or TE events was found to be not only a function of the time spent in AF, but also of the baseline characteristics of the patients.…”
Section: Af Burden and Risk Of Strokementioning
confidence: 99%